Transmission in heteronymous spinal pathways is modified after stroke and related to motor incoordination. - Joseph-Omer Dyer; Eric Maupas; Sibele de Andrade Melo; Daniel Bourbonnais; Jean Fleury; Robert Forget (PLoS ONE, 2009)
Changes in reflex spinal pathways after stroke have been shown to affect motor activity in agonist and antagonist muscles acting at the same joint. However, only a few studies have evaluated the heteronymous reflex pathways modulating motoneuronal activity at different joints. This study investigates whether there are changes in the spinal facilitatory and inhibitory pathways linking knee to ankle extensors and if such changes may be related to motor deficits after stroke. The early facilitation and later inhibition of soleus H reflex evoked by the stimulation of femoral nerve at 2 times the motor threshold of the quadriceps were assessed in 15 healthy participants and on the paretic and the non-paretic sides of 15 stroke participants. The relationships between this reflex modulation and the levels of motor recovery, coordination and spasticity were then studied. Results show a significant (Mann-Whitney U; P<0.05) increase in both the peak amplitude (mean+/-SEM: 80+/-22% enhancement of the control H reflex) and duration (4.2+/-0.5 ms) of the facilitation on the paretic side of the stroke individuals compared to their non-paretic side (36+/-6% and 2.9+/-0.4 ms) and to the values of the control subjects (33+/-4% and 2.8+/-0.4 ms, respectively). Moreover, the later strong inhibition observed in all control subjects was decreased in the stroke subjects. Both the peak amplitude and the duration of the increased facilitation were inversely correlated (Spearman r = -0.65; P = 0.009 and r = -0.67; P = 0.007, respectively) with the level of coordination (LEMOCOT) of the paretic leg. Duration of this facilitation was also correlated (r = -0.58, P = 0.024) with the level of motor recovery (CMSA). These results confirm changes in transmission in heteronymous spinal pathways that are related to motor deficits after stroke.